Gender differences in the relationship between walking activity and sleep disturbance among community-dwelling older adult with diabetes in Taiwan. (4th March 2019) - Cheng, Hui-Ping; Chen, Ching-Huey; Lin, Ming-Hsing; Wang, Chong-Shan; Yang, Yi-Ching; Lu, Feng-Hwa; Wu, Jin-Shang; Lin, Sang-I
ABSTRACT: This study explored the gender differences in the relationship between walking activity and sleep disturbances. A cross-sectional study of 201 community-dwelling older adults with diabetes was conducted in southern Taiwan. Using the Taiwanese version of the International Physical Activity Questionnaire, self-administered short version (IPAQ-SS), information on physical activity and sleep disturbance conditions was collected. Among older female adults with diabetes, 54.2% reported sleep disturbance significantly higher than males (38.1%). Logistic regression analysis suggested that for women, in addition to the active group, older adults in the low-active, high-walking group exhibited a significantly lower rate of sleep disturbance than did those who walked less.